Error Handling In the RavenClaw Dialog Management Framework - Bohus, Dan; Rudnicky, Alexander I. (HLT '05 Proceedings of the conference on Human Language Technology and Empirical Methods in Natural Language Processing, 2005)
We describe the error handling architectture underlying the RavenClaw dialog management framework. The architecture provides a robust basis for current and future research in error detection and recovery. Several objectives were pursued in its development: task-independence, ease-of-use, adaptability and scalability. We describe the key aspects of architectural design which confer these properties, and discuss the deployment of this architectture in a number of spoken dialog systems spanning several domains and interaction types. Finally, we outline current research projects supported by this architecture.